Effect of shear rate on early Shewanella oneidensis adhesion dynamics monitored by deep learning - Lucie Klopffer; Nicolas Louvet; Simon Becker; Jérémy Fix; Cédric Pradalier; Laurence Mathieu (Biofilm)
Understanding pioneer bacterial adhesion is essential to appreciate bacterial colonization and consider appropriate control strategies. This bacterial entrapment at the wall is known to be controlled by many physical, chemical or biological factors, including hydrodynamic conditions. However, due to the nature of early bacterial adhesion, i.e. a short and dynamic process with low biomass involved, such investigations are challenging. In this context, our study aimed to evaluate the effect of wall shear rate on the early bacterial adhesion dynamics. Firstly, at the population scale by assessing bacterial colonization kinetics and the mechanisms responsible for wall transfer under shear rates using a time-lapse approach. Secondly, at the individual scale, by implementing an automated image processing method based on deep learning to track each individual pioneer bacterium on the wall. Bacterial adhesion experiments are performed on a model bacterium (Shewanella oneidensis MR-1) at different shear rates (0 to1250 s−1) in a microfluidic system mounted under a microscope equipped with a CCD camera. Image processing was performed using a trained neural network (YOLOv8), which allowed information extraction, i.e. bacterial wall residence time and orientation for each adhered bacterium during pioneer colonization (14 min). Collected from over 20,000 bacteria, our results showed that adhered bacteria had a very short residence time at the wall, with over 70 % remaining less than 1 min. Shear rates had a non-proportional effect on pioneer colonization with a bell-shape profile suggesting that intermediate shear rates improved both bacterial wall residence time as well as colonization rate and level. This lack of proportionality highlights the dual effect of wall shear rate on early bacterial colonization; initially increasing it improves bacterial colonization up to a threshold, beyond which it leads to higher bacterial wall detachment. The present study provides quantitative data on the individual dynamics of just adhered bacteria within a population when exposed to different rates of wall shear.